Stem Cells and their Potential for Clinical Application - Bilko, Nadja M.; Fehse, Boris; Ostertag, Wolfram; Stocking, Carol; Zander, Axel R.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2008)
This book contains contributions of leading international scientists who participated at the NATO-ASI conference "Stem cells and their potential for clinical application" that was held in Kiev and Simeiz (Ukraine) from August 23 - 31 , 2006. The articles cover a broad range of hot topics in stem cell and leukaemia research. These include the potential of various stem cell types in regenerative and transplantation medicine, different mechanisms of malignant transformation leading to leukaemia development, as well as novel clinical strategies for malignant disease treatment such as adoptive immunotherapy with gene-modified lymphocytes. The mixture of articles by principal scientists from Northern America, as well as Eastern and Western Europe, provides a comprehensive overview on "What's going on?" in various parts of the world in such broadly discussed fields as "stem cell research", "immunotherapy" or "gene therapy". Thus, this compilation should be valuable for readers interested in modern biomedicine who have background knowledge in those areas.
Haematopoietic Stem Cells And Haematopoiesis -- Clonal Dominance after Reconstitution of the Haematopoietic System with Bone Marrow Cells Retroviral -- Function of the Membrane-Bound Isoform Ligands of the Receptor Tyrosine Kinase Subclass III in Inducing Inducing Self-Renewal of Early Hematopoietic Progenitor Cells -- Functional and Phenotypic Heterogeneity of the Human Hematopoietic Stem Cell (HSC) Compartment -- Alterations of Frequency of Hematopoietic Precursors in Mice Subjected to Multiple Courses of Low-Dose G-CSF Injections -- Regulation of Hematopoiesis by Growth Factors -- Biology Of Non-Haematopoietic Stem Cells -- Stem Cell Technologies in Gerontological Research -- Osteopetrotic Models for Identifying Genes that Control Bone Resorption -- Non-Hematopoietic Bone Marrow Cells for Regenerative Medicine -- Epithelial Plasticity of Hepatocytes During Liver Tumor Progression -- Blood Vessels as a Source of Progenitor Cells in Human Embryonic and Adult Life -- Stem Cells And Malignancy -- Stem Cells and Leukaemia -- Telomere and Stem Cell Biology in Chronic Myeloid Leukemia -- Potential Immune Escape Mechanisms of Tumors: MHC Class I Molecules - Enemies or Friends -- The RUNX1 Transcription Factor: A Gatekeeper in Acute Leukemia -- Cell Processing, Expansion and Genetic Modification -- Novel Methodological Approaches in Assessment and Enrichment of Stem Cell Population -- Animal Hybrids and Stem Cells: Their Use in Biotechnology and Clinical Practice -- Cryopreservation of Stem Cells -- The M813 Retrovirus belongs to a Unique Interference Group and is Highly Fusogenic -- Reconstructing an Anti-Tumor Immune Repertoire for Targeted AML Therapy -- Clinical Haematopoietic Stem Cell Transplantation -- Experience of Kyiv Center of Stem Cell Transplantation -- Anti Thymocyte Globuline Allows for Successful Transplantation from HLA Mismatched Unrelated Donors.
Keywords: MEDICINE; ONCOLOGY; IMMUNOLOGY; HEMATOLOGY; CYTOLOGY; MEDICINE & PUBLIC HEALTH; HEMATOLOGY; CANCER RESEARCH; MOLECULAR MEDICINE; CELL BIOLOGY; IMMUNOLOGY